What's the least I can believe and still be a Christian? : a guide to what matters most - Thielen, Martin, 1956- (Louisville, KY : Westminster John Knox Press, 2011)
A national worship and preaching consultant offers a provocative look at the core elements of Christian faith, articulating centrist, mainline Christianity in a way that is fresh and easy to understand.
Part 1: Ten things Christians don't need to believe: God causes cancer, car wrecks, and other catastrophes -- Good Christians don't doubt -- True Christians can't believe in evolution -- Women can't be preachers and must submit to men -- God cares about saving souls but not about saving trees -- Bad people will be "left behind" and then fry in Hell -- Jews won't make it to Heaven -- Everything in the Bible should be taken literally -- God loves straight people but not gay people -- It's OK for Christians to be judgmental and obnoxious -- Part 2: Ten things Christians do need to believe: Jesus' identity : who is Jesus? -- Jesus' priority : what matters most? -- Jesus' grace : am I accepted? -- Jesus' work : where is God? -- Jesus' example : what brings fulfillment? -- Jesus' death : what about suffering? -- Jesus' resurrection : is there hope? -- Jesus' legacy : is the Church still relevant? -- Jesus' promise : who is the Holy Spirit? -- Jesus' vision : what is God's dream for the world? -- A final question : do mainline Christians believe in getting saved?
Keywords: Jesus Christ -- Person and offices; Christianity -- Essence, genius, nature; Jesus Christ; Christianity